On the Experience of Applying the Anagogical Approach to the Formation of Specialists' Information Competence - Larisa Yu. OVSYANITSKAYA; Alexey D. OVSYANITSKIY; Elena A. KONYAEVA; Liliya M. BAZAVLUTSKAYA; Natalya Yu. KORNEEVA; Lyudmila A. KOSTRYUKOVA; Larisa N. PAVLOVA; Olga N. SHVARTSKOP (Communications of International Proceedings, 2020)
The formation of information competence of specialists in any industry is one of the main factors in the process of digital transformation of society. Continuous postgraduate education of people occurs in adulthood. The paper presents the authors' experience related to teaching information technologies based on a scientifically grounded andragogical methodological approach, taking into account the age of the students, social and professional experience. The concept of ‘vitagenic’ experience is discussed. It has been proven that the transition of life experience into vitagenic experience is possible only if life experience has social and value significance and helps to construct the future, taking into account past mistakes and achievements.  Learning information technology for adults on the basis of vitagenic experience contributes to the formation of not only the technical aspects of the issue of mastering digital technology, but also a value, analytical and responsible attitude to information.
Keywords: andragogic approach; continuing education; information competence; vitagenic experience.